Pressure Regulation on A Single Finger of Tri-Finger Pneumatic Grasper Robot using Finite Time and Convergence Prescribed Performance Control - Addie Irawan, Hashim; Mohd Iskandar Putra, Azahar; Mohd Syakirin, Ramli (SIGMA BOT, 2023)
This study presents a method for improving the precision of pneumatic pressure regulation and control in a finger of a tri-finger pneumatic grasper (TPG) robot. The method employs finite time and convergence prescribed performance control (FTC-PPC) in conjunction with proportional, integral, and derivative (PID) control as a strategy to overcome the nonlinearity and uncertainties of pressure regulation of the pneumatic system in the TPG. Besides finite-time tuning, the proposed PPC formulation also introduced convergence rate and domain. To test the method, several experiments were conducted using a 5/3-way pneumatic proportional valve (PPV) configuration with pressure transducers for feedback responses. Two different pressure input patterns, a step, and periodic in-put patterns were used in the experiments. The results show that the proposed controller outperformed the PID as well as the finite-time PPC with PID from the previous works in regulating the pressure for a finger of the TPG by average. 10% in terms of minimizing overshoot, suppressing oscillations, and providing a fast response.